PERANCANGAN SISTEM MONITORING KUALITAS AIR DAN NUTRISI TANAMAN HIDROPONIK BERBASIS ANDROID MENGGUNAKAN NODEMCU ESP32 PADA TANAMAN SELADA (Study kasus : Afflaha Farm) - Ayuningtyas Putri M; Hadi Zakaria (Journal of Research and Publication Innovation, 2023)
Afflaha Farm is a greenhouse engaged in horticultural agriculture and leaf vegetables ranging from land processing, planting, maintenance, and harvesting, and post-harvest activities. The purpose of making this system is The problem that is often experienced by this greenhouse is the lack of attention in providing nutrients and checking the water content needed in hydroponic plants, especially this lettuce so that this plant cannot grow properly and can harm the greenhouse. Thus creating an android-based monitoring system that works to measure water pH levels and provide nutrients. To make the system requires a device in the form of a microcontroller using several sensors such as a pH meter sensor, tds sensor, and wifi module. Using the Java programming language, the C language programming and its data storage use firebase. With this system, it can help farmers get a harvest.